Informational technologies in problems of analysis of high speed melt flows in runner pipes - О. I. Chichko; V. F. Sobolev; S. G. Likhouzov (Литьë и металлургия)
The computer calculations of cast iron flow in industrial foundry goods “Radiator** with different constructive elements of gating systems are carried out. The distributions of total pulse of melt flow on components of velocity vector are calculated. There are offered the characteristics of melt flow for choice of the optimal gating systems constructions.